A new deep-water coral species Telestula ridgensis sp. nov (Scleralcyonacea: Sarcodictyonidae) from the seamount of the Central Indian Ridge - Periasamy, Rengaiyan; Kurian, Palayil John; Ingole, Baban (Zootaxa, 2023)
Telestula ridgensis sp. nov. is a deep-sea octocoral species collected from the Central Indian Ridges (CIR) seamount. The megabenthic communities were sampled from the depths between 1917 and 2053 m using a benthic sledge. It forms part of a baseline environmental and benthic ecological assessment. All these data will be functional in assessing the impact of future massive sulfide mining in the Indian Ocean. We describe a new octocoral species based on integrative taxonomic methods through morphological comparison and molecular phylogenetics. The sclerome of the new species consists of short, stellate plates, crosses, and irregularly shaped and branching forms with dense tubercular ornamentation. The polyp sclerites are arranged in longitudinal rows underneath the tentacles. Two mitochondrial DNA genes (mtMutS and COI) and one ribosomal nuclear DNA gene (28S rRNA) were sequenced to separate the new species. The phylogenetic analyses strongly support the placement of new species in the genus Telestula clade.